2002
DOI: 10.1037/0022-006x.70.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of selected issues in women's reproductive health: Current status and future directions.

Abstract: Emphasizing research published in the past decade, this article presents a summary and evaluation of psychosocial investigations of women's reproductive health, with a focus on selected aspects of menstruation, pregnancy and birth, infertility, and menopause. In some areas, studies have focused on negative physical and psychological concomitants of these health issues. However, research reveals substantial individual variability, with most women adapting well to reproductive health changes. Although methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 292 publications
(371 reference statements)
1
67
0
9
Order By: Relevance
“…There is a significant body of evidence linking psychosocial stress (stressful life events, stress responses, anxiety, appraisals of stress) to a variety of birth outcomes, including lower birthweight and shorter length of gestation (1,16,17). One approach to understanding stress and pregnancy outcomes in African Americans is the theory of allostatic load in which physiologic wear and tear resulting from responses to chronic and repeated acute stress may lead to dysregulation of the body's stress response systems and contribute to negative health outcomes (14,18,19).…”
Section: Stress: a Psychosocial Risk Factormentioning
confidence: 99%
“…There is a significant body of evidence linking psychosocial stress (stressful life events, stress responses, anxiety, appraisals of stress) to a variety of birth outcomes, including lower birthweight and shorter length of gestation (1,16,17). One approach to understanding stress and pregnancy outcomes in African Americans is the theory of allostatic load in which physiologic wear and tear resulting from responses to chronic and repeated acute stress may lead to dysregulation of the body's stress response systems and contribute to negative health outcomes (14,18,19).…”
Section: Stress: a Psychosocial Risk Factormentioning
confidence: 99%
“…Significant within-subject differences were found for bad-tempered (F (3,207 Student-Newman-Keuls post-hoc tests showed that mood is significantly decreased during the menstrual phase.…”
Section: Menstrual Cycle Variations In Cryingmentioning
confidence: 94%
“…The association with distress/discomfort, on the one hand, and the apparent important role of biological, psychological and sociocultural factors makes crying an interesting behavior to study in relation to menstrual cycle variations. Even though it is questionable whether mood varies with menstrual cycle 2,3 , having a menstrual period is not a positive experience either. Most women consider it to be a hassle and cramps and discomforts are frequently reported 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Az egzisztenciális bizonytalanság is egy gyakori stresszor, elsősor-ban a férfi akat érinti, hogy képesek lesznek-e eltartani leendő családjukat. Egy másik félelemként jelentkező stressztényező, amely mindkét félnél egyformán felmerülhet, hogy túlzott felelősséggel járhat a "babaprojekt" [5,6,7]. A mai gazdasági nehézségek között ez érthető, ez a leggyakoribb negatív tényező.…”
Section: öSszefoglaló Közleményunclassified